3‐Trifloxy‐3‐(trifluoromethyl)prop‐2‐ene 1‐Iminium Salts as Precursors for Elusive 3‐(Trifluoromethyl)prop‐2‐yne 1‐Iminium Salts. Issue 23 (18th June 2021) - Keim, Michael; Konetzke, Katharina; Freytag, Angelika; Maas, Gerhard
Abstract: Abstract : 3‐(Trifluoromethyl)prop‐2‐yne 1‐iminium triflate salts were generated from 3‐trifloxy‐3‐(trifluoromethyl)prop‐2‐ene 1‐iminium salts by triethylamine‐assisted elimination of triflic acid and trapped in situ in various cycloaddition reactions. These included Diels‐Alder reactions with 1, 3‐dienes, [2+2] cycloaddition with 1, 4‐diphenylbuta‐1, 3‐diene, and [3+2] cycloaddition with organoazides. All these reactions revealed the excellent dienophilic and dipolarophilic reactivity of the electrophilic C, C triple bond of the novel 3‐CF3 ‐propyniminium salts. Abstract : 3‐(Trifluoromethyl)prop‐2‐yne 1‐iminium triflate salts were generated from 3‐trifloxy‐3‐(trifluoromethyl)prop‐2‐ene 1‐iminium salts by triethylamine‐assisted elimination of triflic acid and trapped in situ in various cycloaddition reactions.